ANALYSIS OF UNDERSTANDING THE CONCEPT OF QUARTERS CLASS VIII STUDENTS ARE ABLE HIGHER MATHEMATICS - Besse Nur Anisa; Alfisyahra; Pathuddin; Rita Lefrida (HISTOGRAM: Jurnal Pendidikan Matematika, 2024)
Understanding students' concepts based on mathematical abilities will provide a framework for teachers to further train students' understanding abilities. This research aims to obtain an analysis of the conceptual understanding of students with high mathematical abilities in class VIII SMP Satu Atap Negeri 2 Toribulu in quadrilateral material. This type of research is qualitative research with a descriptive approach. Data was collected through written assignments and interviews. The results of this research show that the subject has high mathematical abilities, namely being able to restate concepts that have been learned by writing down the similarities and differences using his own language, being able to identify examples and non-examples by stating correct examples and incorrect examples of rhombus shapes, being able to classify objects. -objects according to their properties by explaining that the properties of a rhombus; all sides are the same length, both diagonals are axes of symmetry, both diagonals intersect each other perpendicularly, and the angles facing each other are the same size, and are able to apply the concept or algorithm for solving problems by understanding the meaning of the problem and being able to use a concept of rectangular area to solve problems on the question and explains the steps to solve the problem based on the procedures that have been taught, it's just that there was an error when operating the area of the room.